Spectrum of pulmonary adenocarcinoma with ultrastructural correlation: An autopsy study from northern India - Gupta Kirti; Joshi Kusum; Jindal Surinder; Rayat Charan (Wolters Kluwer Medknow Publications, 2008)
Background: In the present study, we have evaluated the use of electron microscopy in subtyping pulmonary adenocarcinomas, comparing the ultrastructural findings with the diagnosis rendered by light microscopy. Materials and Methods: The gross and histologic features of 16 autopsy cases of pulmonary adenocarcinoma were analyzed and compared with electron microscopic features. The cytologic phenotypes of these cases of well-differentiated pulmonary adenocarcinoma were determined by electron microscopic examination. More than 200 cells in each case were examined, and the tumors were classified according to the predominant feature noted. Results: Eight cases were of Clara cell origin and one case each of type II pneumocyte and bronchial surface cell type. The remaining 6 cases lacked definite discernible features of differentiation towards any specific cell type, other than presence of small nuclear clefts in occasional nuclei. Tumors with Clara cell differentiation were low cuboidal with apical snouts. Type II pneumocyte tumor failed to reveal any characteristic definable as light microscopic feature. Conclusion: Ultrastructural examination is the only definite means of identification of various cell types in the respiratory epithelium and hence forms an invaluable tool in classification of pulmonary adenocarcinoma.